Mosquito Nest Eradication Behavior (PSN) in Communities in Rawabuntu Region South Tangerang - Triana Srisantyorini; PRITHA ERIKA FIHARSHI; Nur Romdhona; Ernyasih Ernyasih (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Dengue Hemorrhagic Fever (DHF) is a disease that always increases and spreads widely. South Tangerang City is the highest city with several 417 cases in 2019. The role of the community is needed to break the chain of transmission using vector control through Mosquito Nest Eradication (PSN) activities. Activities such as eradicating mosquito eggs and larvae using 3M plus. This study was conducted to determine the factors related to the behavior of Mosquito Nest Eradication (PSN) in the Community in the Rawabuntu. The method of research is quantitative analytic with a cross-sectional design, univariate and bivariate analysis, primary data collection by filling out questionnaires using the PPS technique, and then by purposive sampling with an amount of 150 respondents. The result of the chi-square research shows that there is no correlation between knowledge and PSN behavior with a p-value (0,132), there is no correlation between attitudes and PSN behavior with a p-value (0,757), there is a correlation between information availability and PSN behavior with a p-value ( 0,001), there is a correlation between the role of health workers with PSN behavior with p-value (0,011). The result of this study there is no correlation between knowledge and attitudes with PSN behavior, but there is a correlation between the availability of information and the role of health workers with behavior (PSN). It is expected that health workers will provide information and monitor community activities to carry out PSN activities and for the community to make efforts to increase knowledge and attitude regarding PSN by conducting 3M plus regularly to prevent dengue fever.